Interzones : a work in progress - Behrndt, Helle; Benjamin, Walter; Bidjocka, Bili; Bonami, Francesco; Breitz, Candice; Cirincione, Janine; Enwezor, Okwui; Ferraro, Michael; Fuenmayor, Jesús; Merewether, Charles; Michelsen, Anders; Neshat, Shirin; et al. (Kobenhaven : Kunstforeningen, 1996)
Poyo, Txuspo ; Capelán, Carlos ; äda ; Xu Bing ; First, David ; Martorell ; Breitz, Candice ; Delvoye, Wim ; Enwezor, Okwui ; López-Cuenca, Rogelio ; Mesa-Bains, Amalia ; Oguibe, Olu ; Zaya, Antonio ; Kcho ; Sone Yutaka ; Cai Guo-Qiang ; Merewether, Charles ; Neshat, Shirin ; Harris, Lyle Ashton ; Ferraro, Michael ; Udé, Iké ; Park, Kyong ; Bidjocka, Bili ; Vaisman, Meyer ; Costello, Madame ; Holst Henckel, Peter ; Boyce, Sonia ; van Lamsweerde, Inez ; Neuchs, Peter
Interzones : a work in progress, Kunstforeningen, Copenhagen, 22 June - 25 August 1996 ; Uppsala Konstmusuem, Slottet Uppsala, 14 September - 3 November 1996
Engels
boek